Keynote : multi-scale scaffolds for tissue engineering - Neves, N. M. (2012)
A critical issue in the general area of Advanced Therapies is the need for temporary scaffolds to regenerate tissue defects. The scaffolds should be specifically designed to create environments that promote tissue development and not merely to support the maintenance of communities of cells. To achieve that goal, highly functional scaffolds may combine specific morphologies at different scales and dimensions capturing characteristic features and functionalities of the extra-cellular matrix. Many biomaterials have been proposed to produce scaffolds. We have a particular interest in developing systems based in biodegradable polymers. Those demanding applications require a combination of mechanical properties, processability, cell-friendly surfaces and tunable biodegradability that are specific for the application. Electrospinning is a versatile technique used to produce synthetic polymeric ultrafine fibers. It enables the production of non-woven meshes with fiber diameters in the nanometer range with high surface area-to-volume ratio and high porosity. Those meshes can mimic some aspects of the extracellular matrix of human tissues and be used as scaffolds for tissue engineering applications. We developed such structures to obtain the release of bioactive agents intended to direct and control stem cell differentiation. This talk will review our latest developments for bone and cartilage tissue engineering of scaffolds having microstructures at different scales and dimensions.